Pelatihan Public Speaking Berbasis Teknologi untuk Meningkatkan Keterampilan Presentasi di SMA Negeri 2 Semarang: Technology-Based Public Speaking Training to Improve Presentation Skills at SMA Negeri 2 Semarang - Mukhlis, Mukhlis; Mualafina, Rawinda Fitrotul; Budiawan, Raden Yusuf Sidiq; Sunarya, Sunarya; Ulfiyani, Siti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The need for public speaking skills among students, especially in presentations, is the basis for implementing this community service activity. The continued presence of monotonous presentation habits and the inconsistency of content with good presentation standards support the need for this program to be implemented. The purpose of implementing this community service is to optimize students’ public speaking skills, especially in technology-based presentations, at SMA N 2 Semarang. The approach used in this is a community development approach. The stages used in it are 1) experience-based discussions, 2) material presentation (knowledge of public speaking techniques), 3) demonstration of making presentation media based on digital platforms, 4) guided practice, 5) independent practice, and 6) providing feedback and evaluation. Throughout these stages, participants performed well, with an average score of 87. This value is obtained based on assessment aspects, including clarity of delivery, material structure, use of digital media, and self-confidence. This community service program is effective in achieving the stated objectives and contributes to strengthening students’ soft skills, helping them meet the demands of communication in the digital era. Based on all activities, participants have been able to apply interesting and interactive presentation techniques.